Comorbidity in Drivers with Parkinson's Disease. Issue 2 (25th January 2016) - Ranchet, Maud; Tant, Mark; Akinwuntan, Abiodun Emmanuel; Neal, Erin; Devos, Hannes
Abstract : Objectives: To determine the effect of comorbidity on fitness‐to‐drive recommendations that physicians and on‐road driving assessors make and to investigate the agreement in fitness‐to‐drive recommendations between physicians and on‐road driving assessors. Design: Retrospective. Setting: Data on comorbidities associated with Parkinson's disease (PD) and fitness‐to‐drive recommendations were investigated. Participants: Individuals with PD who underwent an official on‐road test in Belgium (N = 72). Measurements: Correlations between comorbidity and fitness‐to‐drive recommendations were calculated. Stepwise logistic regression models were used to investigate whether comorbidity was an independent predictor of fitness‐to‐drive recommendations (pass/fail) that the physicians or the on‐road assessors made. The percentage of agreement and the prevalence and bias‐adjusted kappa (PABAK) were used to investigate agreement between the physicians and the on‐road assessors. Results: Moderate correlations were found between comorbidity and fitness‐to‐drive recommendations that the physicians ( ρ = 0.34, P = .004) and the on‐road assessors ( ρ = 0.30, P = .01) made. Comorbidity was the most important determinant (coefficient of determination = 0.16, P = .005) of the physicians fitness‐to‐drive recommendations. No significant effect of comorbidity on the on‐road recommendations was found. The physicians and the on‐road assessors agreed in 46 (64%) of the cases (PABAK = 0.46, P < .001). Conclusion: Comorbidity plays a role in physicians' recommendations of fitness to drive that may explain, in part, inconsistencies between physicians and on‐road assessors' fitness‐to‐drive recommendations. This study indicates the need for an interdisciplinary dialogue between physicians and on‐road assessors to reach a comprehensive fitness‐to‐drive decision.